1994
DOI: 10.1111/j.1469-8137.1994.tb07531.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of O3 and SO2 on reproductive development in oilseed rape (Brassica napus L.)

Abstract: SUMMARY The flowering racemes of Brassica napus L. cv. Tapidor were exposed independently from the vegetative component to 200 nl l−1, 100 nl l−1 O3/30 nl l−1 SO2, In all cases, a single 6 h exposure significantly increased bud abortion, and abscission 2 and 5 d after treatment. Similar results were obtained using cv. Libravo, although the effect of 100 nl l−1 O3 was significant only after 2 d. Exposure to 30 nl l−1 SO2 did not enhance bud abortion and abscission in either variety. Longer term measurements for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…By contrast, Bergmann et al (1996) showed that the timing of flowering and seed set were not significantly affected by seasonlong exposure to 1.5 times the ambient ozone concentration in 17 herbaceous species relative to plants experiencing ambient concentrations. Similarly, direct exposure of the inflorescences to ozone had no significant effect on the timing of bud and flower opening in B. napus (Bosac et al, 1994) and B. campestris (Stewart, 1998), or on floral morphology or development and the duration of flowering in P. major (Stewart, 1998). The impact of ozone on the timing of flowering therefore varies markedly between species.…”
Section: Floral Initiation and Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…By contrast, Bergmann et al (1996) showed that the timing of flowering and seed set were not significantly affected by seasonlong exposure to 1.5 times the ambient ozone concentration in 17 herbaceous species relative to plants experiencing ambient concentrations. Similarly, direct exposure of the inflorescences to ozone had no significant effect on the timing of bud and flower opening in B. napus (Bosac et al, 1994) and B. campestris (Stewart, 1998), or on floral morphology or development and the duration of flowering in P. major (Stewart, 1998). The impact of ozone on the timing of flowering therefore varies markedly between species.…”
Section: Floral Initiation and Developmentmentioning
confidence: 99%
“…§Indicates that only the inflorescences were exposed to ozone ; the vegetative and reproductive organs were both exposed in all other studies. Bosac et al, 1993Bosac et al, , 1994Bosac et al, , 1998, Wisconsin Fast Plants (Brassica campestris ; Stewart et al, 1996 ;Stewart, 1998) and P. major (Stewart, 1998) provide evidence that exposure to realistic ozone episodes at critical developmental stages can influence the reproductive structures directly, promoting significant effects on floral development, seed yield and quality, and seedling vigour. These studies also demonstrated substantial genotypic variation in sensitivity, and the existence of extensive compensatory flexibility which enables reproductive sites lost by abortion or abscission to be replaced, thereby contributing to the maintenance of seed yield.…”
Section:      mentioning
confidence: 99%
See 3 more Smart Citations